Kontribusi Kemampuan Penalaran dan Self-Efficacy terhadap Kemampuan Pemecahan Masalah Siswa - Dita Aldila Krisma; Agus Maman Abadi (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
This research aims to describe the effect of reasoning ability and problem-solving ability, the effect of self-efficacy and problem-solving ability, and the effect of reasoning ability and self-efficacy on the problem-solving ability of junior high school students. This research was correlational descriptive research. The population of this research is 8th-grade students in one of the junior high school in Bantul. The research sampling technique was used to take the sample in this research is purposive random sampling which was obtained 20 students from grade 8A. The data was obtained using 2 ways named test and non-test. Test instrument in the form of essay problem to obtain reasoning ability and problem-solving ability data. While, non-test instrument in the form of questionnaire to obtain self-efficacy. The data were analyzed using multiple linear regression. The result of this result is there is the effect of reasoning ability on problem-solving ability belongs to very low category and the effect is not significant , there is the effect of self-efficacy on problem-solving ability belongs to strong enough category besides the effect is significant. Besides, the effect of reasoning ability and self-efficacy is positive on problem solving-ability as much as 49.3%, while the remainder is 50.7% was affected by other variables.